Robert Staughton Lynd and Helen Merrell Lynd papers - Lynd, Robert Staughton, 1892-1970.; Lynd, Helen Merrell, 1896-1982.
Correspondence, writings and lectures, notes, research materials, student papers, and miscellaneous biographical and genealogical material chiefly relating to the Lynds' sociological research and writings, especially their "Middletown: A Study in Contemporary American Culture" (1929). Other topics include academic and educational affairs at Columbia University and Sarah Lawrence College, national security questions and academic freedom, and the Social Science Research Council. Correspondents include Crane Brinton, Sigmund Diamond, Erik Erikson, Robert K. Merton, David Riesman, and Lynd (Lynn) family members.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Sociologist and educator. Married Helen Merrell, also a sociologist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brinton, Crane, -- 1898-1968 -- Correspondence; Diamond, Sigmund -- Correspondence; Erikson, Erik H. -- 1902-1994 -- Correspondence; Merton, Robert King, -- 1910-2003 -- Correspondence; Riesman, David, -- 1909-2002 -- Correspondence; Lynn family; Columbia University; Sarah Lawrence College; Social Science Research Council (U.S.); Academic freedom; Internal security; Social sciences; Sociology; Universities and colleges -- New York (State); Educators; Sociologists